Optimasi Penggunaan Faktor - Faktor Produksi pada Usahatani Apel (Studi Kasus di Desa Andonosari, Kecamatan Tutur, Pasuruan): Optimization of Use of Production Factors on Apple of Farming (Case Study in Desa Andonosari, Kecamatan Tutur, Pasuruan) - Putri, Devi Laxmi Aprilia; Nurhadi, Eko; Soedarto, Teguh (Jurnal Ilmiah Manajemen Agribisnis, 2024)
The use of farming production factors that are not done as well according to their recommendations, will have an impact on the optimal level that will be achieved by farmers. This study aims to measure the level of optimization of the use of apple production factors, knowing the strategy of developing apple farming in optimizing the use of apple production factors. The method of determining the sample is simple random sampling with a sample size of 60 farmers. The method of data analysis is multiple linear regression analys, the ratio of the value of marginal products to the prices of inputs and swots. The results show that technically, seeds, manure, chemical fertilizers, liquid pesticides, and labor have been efficient. All allocatively and economically all factors of production have not been efficient. Factors of seed production, manure and liquid pesticides can be considered rationally to increase or decrease the use of production factors in order to achieve optimal levels. In the swot diagram, the strategy position lies in quadrant I, which is an aggressive strategy. The right strategy is the S-O strategy, which uses all the strength factors to take advantage of opportunities.